PENDEKATAN KOMUNIKASI SMCR DALAM PERANCANGAN PERMAINAN BOARD GAME ULAR TANGGA “POSTCOV” UNTUK UPAYA MEMBANTU TRAUMA HEALING ANAK PADA PANDEMI COVID-19 - Dzuha Hening Yanuarsari; Mukaromah Mukaromah; Khamadi Khamadi (LPPM Institut Bisnis dan Teknologi Indonesia, 2021)
The Covid-19 pandemic that occurred at the end of 2019 had a significant impact on various sectors of activity in the world, including Indonesia. Various actions were taken as steps to overcome these problems. One of them is in the education and health sector for children, namely the psychological vulnerability of children and the level of depression that occurs due to the Covid-19 pandemic phenomenon. Through educational games, it is believed that it can help things related to child psychology. The purpose of this research is to create an educational game of snakes and ladders that can be used to help the trauma healing process in children due to the impact of the Covid-19 pandemic. The research method used in this design is an explanatory descriptive method using the SMCR communication approach. Through this method, educational messages regarding the COVID-19 pandemic that children still have to deal with should be treated with caution and there is no need to be afraid as long as they adhere to health protocols. The results of this study are the creation of a prototype design of the snake and ladder game